On analysis and design of discrete-time constrained switched systems*. Issue 2 (1st February 2018) - Souza, Matheus; Fioravanti, André R.; Shorten, Robert N.
ABSTRACT: This paper presents novel design techniques for discrete-time constrained switched systems. Two problems are considered: the first one is centred at determining a set of switching rules for which the system is unconditionally stable; the second one focuses on the design of a stabilising state-dependent switching function that is subject to structural constraints. Convex optimisation is the kernel of the devised procedures and, thus, these techniques are computationally viable.